Quantification of the Magnetic Anisotropy of a Single‐Molecule Magnet from the Experimental Electron Density. (16th September 2020) - Damgaard‐Møller, Emil; Krause, Lennard; Tolborg, Kasper; Macetti, Giovanni; Genoni, Alessandro; Overgaard, Jacob
Abstract: Reported here is an entirely new application of experimental electron density (EED) in the study of magnetic anisotropy of single‐molecule magnets (SMMs). Among those SMMs based on one single transition metal, tetrahedral Co II ‐complexes are prominent, and their large zero‐field splitting arises exclusively from coupling between the d x 2 - y 2 and dxy orbitals. Using very low temperature single‐crystal synchrotron X‐ray diffraction data, an accurate electron density (ED) was obtained for a prototypical SMM, and the experimental d‐orbital populations were used to quantify the dxy ‐d x 2 - y 2 coupling, which simultaneously provides the composition of the ground‐state Kramers doublet wave function. Based on this experimentally determined wave function, an energy barrier for magnetic relaxation in the range 193–268 cm −1 was calculated, and is in full accordance with the previously published value of 230 cm −1 obtained from near‐infrared spectroscopy. These results provide the first clear and direct link between ED and molecular magnetic properties. Abstract : The experimental electron density obtained from 20 K synchrotron X‐ray diffraction data was used here to quantify the zero‐field splitting parameter in a Co II ‐based single‐molecule magnet. The methodology uses the d‐orbital populations to derive the ground‐state wavefunction composition, which is shown to be strongly correlated to the zero‐field splitting.